Dinâmica populacional do pargo, Lutjanus purpureus Poey, 1875 (Pisces: Lutjanidae) na plataforma norte do Brasil - SOUZA, Rosália Furtado Cutrim (2002)
Growth, mortality, biometry and reproduction of the red snapper, Lutjanus purpureus was researched from samples obtained from landings of commercial catches in the northern Brazilian coast with auspicious of REVIZEE program and Biology and Fishing of the red snapper in the northern Brazilian Project of the CEPNOR/IBAMA . Total and zoological length data obtained from approximately 500 individuals were collected monthly in the cities of Belém, Vigia and Bragança, from January 1999 to December 2000. Sub-samples of 150 fishes were obtained monthly from April 1998 to January 2000 to study reproduction and biometry. In the CEPNOR/IBAMA laboratory were carried out biometry, identification of sexy type and gonadal maturation stages. The total of 16. 733 specimens, presents percentile superiors at 50% of young individuals. The amplitude of total class varied from 13 to 112 cm of length and the length averages were 45,72 cm and 51,91 cm, respectively for the year of 1999 and 2000. The morphometric and weight/length relationships show positive allometry. The weight/length relation of male and female differ significantly from Student statistic method. The reproduction was researched determining the sexual proportion under chisquare statistics, the size of first maturation and spawning period, that was analyzed temporal variation of frequency of the gonadal stages and gonadal-somatic relation. The whole research period was observed a female predominance in the month analysis only in April 1998, May and June 1999 do not present significant differences between male and female. In sexual proportion, by class length the predominance of female was highly significant from 28 to 45 cm. The total length class of first maturation was estimated between 43 a 46 cm from females by graphic extrapolation method and the 43,67 cm by adjust of Galton ogive. The reproductive period was defined in two points, one more intense in the second quarter of the year, with a larger amplitude in may/1998 and another one reduced in the fourth quarter same year. Growth parameters were estimated by ELEFAN I system, Bhattacharya, Gulland & Holt and Appeldoorn methods in FiSAT program. The Appeldoorn method presents the better adjust to red snapper with value of L= 115 cm, K= 0,091 year-1, and determine von Bertalanffy equation Lt = 115 (1-e 0,091t-to). The natural mortality was estimated in 0,25 year-1 e 0,31 year-1 by Pauly and Rikhter & Efanov equations, respectively. The total mortality estimated by converted length in curve of linearized catch and Beverton & Holt method reached values of 0,59; 0,664 respectively. Mortality by fishing and exploitation rate were also calculated and obtained values F = 0,34 year1 e E = 0,57. The longevity estimated by Taylor equation was 33 years. The red snapper presents slow growth and longevity life with periodic spawn. The fishing in the northern Brazilian coast happen high percentile of young fishes. That can contribute to overfishing growth , compromising the sustentability of the species and the fishing activity in the northern Brazilian coast. It is indispensable to adopt regulation measures to red snapper fishing, at least about minimum size capture.